2020
DOI: 10.1002/pc.25822
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of tapered carbon‐fiber‐reinforced polymer rim for carbon/aluminum assembled wheel

Abstract: A multi‐objective integrated optimization framework that considers the manufacturing process in the design of a tapered carbon‐fiber‐reinforced polymer (CFRP) rim structure was established. Firstly, the three‐zone symmetrically stacked CFRP rim structure was proposed and modeled. The bending and radial fatigue and 13° impact of the carbon/aluminum‐assembled wheel composed of CFRP rim and aluminum alloy spoke were analysed. Coupling lay‐up thickness, sequence and angle as design variables, multi‐objective integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Based on the experimental results, it was found that the laminated structure has better penetration resistance against the flat head projectile, and the placement of an aluminum plate on the impact surface can change the failure mode of carbon fiber laminates and improve the energy absorption level of composite plates. On a component level application, Wang et al 31 established a multi‐objective integrated optimization framework considering for the fabrication of a tapered rim composed of CFRP rim and aluminum alloy spoke. In most of the literature AA 2024‐T3 has been used for the fabrication of FMLs 7,32–39 .…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…Based on the experimental results, it was found that the laminated structure has better penetration resistance against the flat head projectile, and the placement of an aluminum plate on the impact surface can change the failure mode of carbon fiber laminates and improve the energy absorption level of composite plates. On a component level application, Wang et al 31 established a multi‐objective integrated optimization framework considering for the fabrication of a tapered rim composed of CFRP rim and aluminum alloy spoke. In most of the literature AA 2024‐T3 has been used for the fabrication of FMLs 7,32–39 .…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…However, to make NSGA‐II better handle multiobjective optimization problems, NSGA‐II can be modified. The Modified NSGA‐II algorithm has good results in handling multiobjective problems 26 . Khalkhali 27 used a MNSGA‐II to conduct a multiobjective analysis of the S‐rail of the car by taking the absorbed energy ( E ), peak crushing force ( F max ), and structural mass ( W ) as objective functions.…”
Section: Introductionmentioning
confidence: 99%
“…The Modified NSGA-II algorithm has good results in handling multiobjective problems. 26 Khalkhali 27 used a MNSGA-II to conduct a multiobjective analysis of the S-rail of the car by taking the absorbed energy (E), peak crushing force (F max ), and structural mass (W) as objective functions. Optimization to reduce the vehicle weight while reducing passenger injuries in collision events.…”
Section: Introductionmentioning
confidence: 99%
“…Following nal layup optimization, the authors achieved a theoretical weight reduction of 18% over an identical aluminium wheel. Wang et al [13] conducted a detailed design optimization and analysis of a hybrid wheel using a CFRP rim and aluminium disc. A multi-objective optimization algorithm was employed to optimize layup thickness, sequence, and angle.…”
Section: Introductionmentioning
confidence: 99%